Regulatory, technical, and safety considerations for UAV-based inspection in chemical process plants: A systematic review of current practice and future directions - Sairul Safie; Raudhah Khairil (Transportation Research Interdisciplinary Perspectives)
Chemical process plants require frequent inspection to ensure operational safety and prevent equipment failure. In recent years, the use of UAVs for inspecting chemical process plants has gained significant attention due to their ability to provide more efficient, cost-effective, and safer inspection services. This review article provides a comprehensive analysis of the current practice and future directions of UAV-based inspection in chemical process plants, with a focus on the regulatory, technical, and safety considerations. The review searched for studies on UAV standards in chemical process plants using multiple databases and specific keywords. Two stages of search were conducted, including a full-text review, and inclusion and exclusion criteria were applied to select relevant studies published in English between 2013 and 2023. Data on UAV standards were extracted, including benefits, limitations, national as well as international standards, challenges, and opportunities. A narrative synthesis approach was used to summarize the findings of the studies in a descriptive manner. The implications of this review are significant, as they provide a comprehensive understanding of the benefits and limitations of using UAVs for inspection in chemical process plants. The review highlights the need for continued research and development in this area to address technical and safety challenges and to facilitate wider adoption of UAV-based inspection technologies in chemical process plants.